Influence of Stress to Achievement Motivation and SWB: Basis for a CBT-Based Program - Mary Jane Galang (Philippine Association of Institutions for Research, Inc., 2023)
The college years are stressful for many students. Their sources of stress include pressure from academic, family problems, and social, emotional, and physical stressors. Lack of ability to withstand stress leads to new behavioral patterns, resulting in further stress and problems. Thus, the student's failure to resolve problems causes ongoing emotional conflicts that affect their wellbeing and reduce achievement motivation. This study investigated the relationship of stress on achievement motivation and subjective well-being among twenty-two student scholars from the De La Salle University in Manila and Laguna, Philippines. Using quantitative correlational research design, three assessment tools were used to measure the variables: Revised-Achievement Motivation Scale, Satisfaction with Life Scale [SWLS], and Positive Affect-Negative Affect Scale [PANAS]. The Stress data was culled from the SAS1000 Course Module containing a Stress Test.  Data analysis revealed a nonsignificant and positive relationship between stress and achievement motivation (r=.093; P=.681); a significant negative relationship between stress and satisfaction with life (r=-.474; P=.026), a nonsignificant negative relationship between stress and Positive Affect (r=-.056; P=.805); and a nonsignificant positive relationship between stress and Negative Affect (r= .178; P=.428). Findings showed that the student scholars' stress is significantly related to satisfaction with life which is the cognitive component of SWB. These data will serve as a basis for developing a Cognitive Behavioral Therapy-based program for the Student Scholars.